THE EFFECTIVENESS OF BINGO GAME ON THE FIFTH GRADERSâ VOCABULARY MASTERY - Munawaroh, Nila Shofyatul (Pusat Pengembangan Bahasa IAIN Tulungagung, 2016)
Learning vocabulary at elementary school means the students get some vocabularies. The teacher introduces the new word to the students and makes the students memorize the vocabulary. Bingo Game is one of technique in teaching vocabulary. This game can be practiced by asking students to remind words they have remembered after the lesson. This study aimed at knowing the effectiveness of Bingo Game to teaching vocabulary at elementary school. The research design of this research was pre-experimental research design by using one group pre-test post-test with quantitative approach. The fnding of this study showed that the mean score of the students after they are taught by using Bingo Game (92.80) was higher than before they are taught by using Bingo Game (75.60). Statistical computation using T-test showed that the score of tcount was higher than ttable (7.247 > 2.021) with standard signifcant 5% and degree of freedom was 32. It was concluded that Bingo Game is effective to teach vocabulary at elementary school.